Dementia and mild cognitive impairment in patients with Parkinson's disease - Tedrus,Gloria Maria Almeida Souza (2009)
The objective of this research was to assess the occurrence of cognitive impairment in 32 individuals (average age: 67.2 years old) with Parkinson' disease (PD). Procedures: clinical-neurological assessment; modified Hoehn and Yahr staging scale (HYS); standard neuropsychological battery of CERAD (Consortium to Establish a Registry for Alzheimer' Disease); Pfeffer questionnaire; and Clinical Dementia Rating. A comparison was made with a control group (CG), consisting of 26 individuals with similar age and educational level but without cognitive impairment. The PD patients showed an inferior performance in the CERAD battery when compared to the CG. Three PD sub-groups were characterised according to cognition: no cognitive impairment - 15 cases; mild cognitive impairment - 10; dementia - 7 cases. There was a significant association between motor disability (HYS) and the occurrence of dementia. Dementia and mild cognitive impairment frequently occur in PD patients and should be investigated in a routine way.